Social demands and citizenship: The case of Quispicanchi-Cusco - Sulmont Haak, David (1995)
This article is actually a fragment of our undergraduate thesis in sociology. The main objective of this work was to present the relations between "citizens" and the State in a rural context: how the social groups of power that are established in that space are structured, the demands presented by the different actors, the form of negotiation of the same and the impact of the action of the State in that context, as well as the transformations that it introduces in the rural social structure.